Application of magnetic analyzers for detecting carburization of pyrolysis furnace tubes - Du, Chenyang; Liu, Chang; Li, Xiaowei; Liu, Baolin; Lu, Jianyu; Tan, Xinli; Song, Ce (Frontiers in Materials, 2023)
Ethylene pyrolysis furnace is a key equipment in the ethylene production industry with the pyrolysis furnace tube being the core component of this system. Due to harsh operating conditions, the furnace tube becomes susceptible to carburization and creep, which are the major causes of tube failures. Hence, non-destructive testing (NDT) methods such as vortex and ultrasonication have been applied for detecting carburization of the tube. Since tubes manufactured using HP series materials undergo paramagnetic to ferromagnetic transformation upon carburization, the tube coercivity can be used to ascertain the thickness of the carburization layer. In this study, a portable magnetic analyzer is used to measure the tube coercivity, and the relationships between the thickness of carburization layer and coercivity are obtained. Results show that the proposed method is effective for NDT of carburization in pyrolysis furnace tubes.